Case report: Sarcomatoid renal cell carcinoma masquerading as hydronephrosis - Chen, Shicheng; He, Zhongcong; Meng, Mi; Tian, Zhong; Zhu, Cheng; Fu, Ni; Yu, Bo (Frontiers in Oncology, 2024)
Sarcomatoid renal cell carcinoma (SRCC), a manifestation of sarcomatoid dedifferentiation in renal cell carcinoma, is characterized by elevated invasiveness and a grim prognosis. Typically, SRCC patients present with advanced or metastatic conditions and survival rates rarely extend beyond one year [1]. In this study, we describe a case of SRCC characterized by the patient exhibiting right flank pain without hematuria. Initially, imaging interpretations led to a diagnosis of severe hydronephrosis.Subsequently, an open right nephrectomy post-surgery confirmed the pathology of sarcomatoid renal cell carcinoma.